ESTIMATING ECONOMIC VIABILITY OF IRRIGATED RICE FARMING AMONG HOUSEHOLDS IN A TYPICAL FLOOD PLAIN IN NIGERIA - Dimas, Phillip; Ja'afar-Furo, Muhammad R (Agricultural Socio-Economics Journal, 2024)
This paper examines the economic viability of irrigated rice production as a stable crop among farming households on Lake Gerio flood plains in Adamawa State, Nigeria, using 81 farm families selected randomly as respondents. Primary data collected through cost route by application of questionnaire were subjected to descriptive statistics, gross margin analysis, multiple regression analysis and allocative efficiency of resources to achieve stated objectives. Findings reveal married male households’ heads dominating (90.1%) the farming population, with a larger proportion (35.8%) owning 1.0 ha-2.0 ha of farmland. A Gross Margin (GM) of N119, 319 was recorded per hectare, signifying a viable economic activity for the farming households. Farm size (p < .001), labour (p < .001), educational level of farmers (p < .005) and quantity of fertiliser (p < .005) were found to be statistically significant in influencing yield of the crop. Cost of inputs (60.5%), inadequacy of funds (45.0%) and incidence of pests and diseases (22.2%) were the most experienced constraints among farm families. Conclusively, rice irrigation farming on Lake Gerio flood plains was profitable. Private and public institutions should intensify provision of credible extension services and making inputs available to farmers at subsidised costs.